Investigating the effect of Gotvand Dam on changes in soil salinity and vegetation cover of downstream lands of the dam using satellite imagery and spectral indices - Morteza Sharif; Saeid Hamzeh (علوم محیطی)
Introduction: One of the most important factors that play a major role in reducing soil fertility and agricultural land degradation is soil salinization. Soil salinity problem is more severe in agricultural lands of arid and semi-arid regions. In many cases, human activities and irrigation of agricultural lands with saline water are the cause of salinization. This is a serious problem in different regions of Iran, especially in Khuzestan Province. Therefore, the present study was conducted with the aim of monitoring and evaluating the effect of Gotvand Dam on the salinization of the downstream area and changing its plant ecosystem before and after water intake using remote sensing imagery.Material and methods: The time series of two ETM+ and OLI sensors from 2019-1999 were collected using plant indices (NDVI, SAVI), biophysical index of leaf cover (LAI), and salinity indices. The soil was classified by salient decision-making method of changes in halophyte and non-halophyte plants according to the threshold obtained from the indicators used in each year. Then, the final results were evaluated according to the trend of changes obtained from the used indicators and their correlation with changes in the plant ecosystem of the region.Results and discussion: The rate of vegetation changes in the four years of 2018, 2013, 2002, and 1999 was more than other years, which was prepared by the method of supervised classification of the area under normal vegetation and saline plants. According to the results obtained from 1999, the total vegetation area of the groves was about 1117 hectares, of which about 134 hectares were related to halophyte vegetation. However in 2018, these values were estimated at 921 hectares, with areas covered by halophyte changing to 445 hectares and halophyte to 476 hectares.Conclusion: The results of the study indicate the onset of the highest stresses in the plant ecosystem of the region and the simultaneous decline in leaf cover and NDVI with the water intake of Gotvand Dam since 2011. This coincidence, which is due to the salinity of the water of Gotvand Dam Lake and consequently Karun River, has a significant effect on increasing salinity and changes in soil quality of the region and thus increasing halophyte plants as well as high vegetation degradation in the region. These conditions can create more serious challenges for the ecosystem of this area and in the long period change the ecosystem and vegetation cover of this region to halophyte plants.